2012
DOI: 10.1055/s-0032-1312581
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intensity and Lymphocyte Subset Apoptosis

Abstract: This investigation assessed the lymphocyte subset response to increasing intensity. Participants completed an exertion test (VO(2max)), and later performed a 10-min run at 76% VO(2max), 5-min at 87%, and run to exhaustion at 100% intensity. Blood was sampled at rest, following each intensity, and 1-h post. Cell concentration, apoptosis (annexin V) and migration (CX₃CR1) were evaluated in CD4+, CD8+, and CD19+ subsets. Relative data were analyzed using 1-way ANOVA with significance at P≤0.05. Absolute changes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 25 publications
5
33
1
Order By: Relevance
“…Although Treg cell death was not measured in this study, a recent study (Krüger et al 2016) found that continuous aerobic exercise (30 min of cycling at 70% V O 2max ) elicits apoptosis in peripheral Tregs, which lends some support to this idea. Exercise-induced Treg cell apoptosis would also be wholly consistent with the effects of aerobic exercise on other T-cell sub-populations (Krüger et al 2016; Navalta et al 2013). Alternatively, it is also important to consider that the decrease in circulating Tregs simply reflects the fact that they were rapidly distributed to other tissues after the marathon, as suggested with other T-cells populations (Krüger et al 2016; Krüger et al 2008).…”
Section: Discussionsupporting
confidence: 61%
“…Although Treg cell death was not measured in this study, a recent study (Krüger et al 2016) found that continuous aerobic exercise (30 min of cycling at 70% V O 2max ) elicits apoptosis in peripheral Tregs, which lends some support to this idea. Exercise-induced Treg cell apoptosis would also be wholly consistent with the effects of aerobic exercise on other T-cell sub-populations (Krüger et al 2016; Navalta et al 2013). Alternatively, it is also important to consider that the decrease in circulating Tregs simply reflects the fact that they were rapidly distributed to other tissues after the marathon, as suggested with other T-cells populations (Krüger et al 2016; Krüger et al 2008).…”
Section: Discussionsupporting
confidence: 61%
“…As we expected the absolute change from rest with regard to apoptotic and migratory markers to be similar to the change in cell volume, the Chi squared test (χ 2 ) was utilized. As previously described, based on our previous investigation [ 7 ] , a large eff ect size was anticipated. However, to employ a conservative approach, sample size was calculated using a medium eff ect size corresponding to a 25 % relative increase in post-exercise apoptosis.…”
Section: Statistical Analysesmentioning
confidence: 75%
“…Previous investigations have investigated cell markers of apoptosis and migration following a progressive treadmill protocol to exhaustion [20], an endurance run on the treadmill for 2 h at 65% VO 2max [21], a treadmill protocol increasing intensity [10], repeated Wingate cycle tests [22], and a downhill running protocol [23]. Recently, Navalta et al [10] assessed the lymphocyte subset response to increasing intensity (10 min run at 76% VO 2max , 5 min at 87%, and run to exhaustion at 100% intensity). Cell concentration, apoptosis (annexin V), and migration (CX 3 CR1) were evaluated in CD4+, CD8+, and CD19+ subsets at rest, following each intensity, and 1 h later.…”
Section: Discussionmentioning
confidence: 99%
“…To note, annexin V (member of the annexin family of intracellular proteins) that binds to phosphatidylserine has been widely used to identify apoptotic cells [9]. Nevertheless, the movement of cells from the circulation (migration) is another possible contributing mechanism to postexercise lymphocytopenia [10]. This migration process may be identified by the expression of CX3CR1 (CX3C chemokine receptor 1), since the interaction of CX3-CR1 with its ligand mediates cell adhesion and migration [11].…”
Section: Introductionmentioning
confidence: 99%